ANTIBACTERIAL ACTIVITY OF PATCHOULI OIL REFINERY WASTE AGAINTS STAPHYLOCOCCUS AUREUS BACTERIA - Sarmila, Sarmila; Razak, Abd. Rahman; Jamaluddin, Jamaluddin (Fakultas Farmasi, Universitas Muslim Indonesia, 2022)
Patchouli oil refining waste is biomass or organic waste which has chemical contect so that it has antibacterial potential. This study aims to determine the antibacterial activity of patchouli oil refining waste against Staphylococcus aureus and knowing the groups of compounds identified as having antibacterial activity after the TLC Bioautography test was carried out. The sample was extracted using the maceration method with 96% ethanol solvent. Antibacterial activity testing was carried out with a concentration variant of 50%, 25% and 10% with the well method. Thin layer Chromatography (TLC) using n-hexane : ethyl acetate (3:1) elucants. TLC Bioautography using contact bioautography method. From the research that has been done, it is found that the ethanol extract of patchouli oil refining can inhibit Staphylococcus aureus which has the largest diameter of resistance with a concentration of 50% which is categorized as very strong. The results of the TLC Bioautography study showed the saponin compound class after being sprayed with H2SO4 10% reagent, it was found that the ethanol extract of patchouli oil refined pulp has antibacterial activity against Staphylococcus aureus and compounds to play a role in antibacterial activity are saponins.